Comprehensive Review of Personalized Nursing Care, Technological Integration, and Workforce Resilience in Modern Healthcare - Alyami, Hamad Qassas Hamad; Alyami, Hamdeh Saleh Ali; ALHindi, Etidal Saeed Hadhrami; Abdullah, Fatma Hadi Ali; Alsaad, Seham Saleh; Almahri, Sairah Salem; Ayda, Mariam Demshik; Alzoqozq, Namah Abdullah Masoud; Alsoqoor, Aziza Ali Ahmad; Alsagoor, Meseadah Ali Salman (Journal of Ecohumanism, 2024)
The dynamic sphere of concern requires a complex solution based on the elements of the individual approach to the patients, the application of the technologies into the nursing practice, and the promotion of such factors as staff retention and workplace satisfaction. Cultural sensitivity allows the patient to get personalized care that addresses his or her needs, / preferences and beliefs. In addition, there are adoption and use of solutions like Electronic Health Records (EHRs) and Telehealth that have changed how service is delivered. Though these advancements come at costs such as exhaustion and skills deficit of nurses, the Future wellbeing of human health requires an imperative focus on workforce endowment. This paper looks at the relationship between these key parameters and their effects on the health delivery system and future potential solutions.